Problematika Pemberian Diskresi dan Impunitas kepada Pemerintah Terkait Kebijakan Keuangan Negara dalam Penanganan Pandemi Covid-19 - Saharuddin; Asmar, Abd. Rais; Natsif, Fadli Andi (Universitas Islam Negeri Alauddin Makassar, 2023)
This study analyzes the use of discretion and impunity in the management of state finances during the COVID-19 pandemic. The results showed that regulation No. 1 of 2020 which became law No. 2 of 2020 is contrary to the principle of the rule of law because it abolishes criminal and civil sanctions for officials who harm the state. This has implications for the state budget. Normative research with data collection from library sources was used in this study. Overall, this study concludes that discretion and impunity in the management of state finances during the COVID-19 pandemic are contrary to the principles of the rule of law and have an impact on the state budget.